Methodical aspects and measuring set-up for investigation the ability to selective detection of different ionizing radiations by organic scintillators - Galunov, N.Z.; Martynenko, E.V.; Tarasenko, O.A. (Functional Materials, 2006)
In this paper, we have discussed the technique for selective detection of different types of ionizing radiations. This technique is based 011 the discrimination procedure of particles by their scintillation pulse shape. We have studied the ability of organic crystalline and liquid scintillators to selective detection of neutron and y-radiation. The results we have been obtained in this work give initial information for the quantitative analysis of the processes proceeding in side a particle track in contrast to earlier works when such a study, in fact, had qualitative character.